2015
DOI: 10.2147/dddt.s81390
|View full text |Cite
|
Sign up to set email alerts
|

Paclitaxel attenuates renal interstitial fibroblast activation and interstitial fibrosis by inhibiting STAT3 signaling

Abstract: Recent studies have demonstrated that paclitaxel might inhibit renal fibrosis. However, the underlying molecular mechanism remains unclear. In this study, we hypothesized that low-dose paclitaxel may block the STAT3 (signal transducer and activator of transcription 3) signaling to attenuate fibrosis in a mouse model with unilateral ureteral obstruction. Both NRK-49F cells and mice with unilateral ureteral obstruction were treated with paclitaxel. The results showed that paclitaxel treatment resulted in a dose-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
57
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(61 citation statements)
references
References 31 publications
4
57
0
Order By: Relevance
“…This result is in agreement with the literature as PAT significantly decreases the SM a-actin expression. 21,22 Also, in this study, no significant difference in the SM a-actin expression was observed between the cells treated with Cremophor-PAT and nab-PAT.…”
Section: Sem and Osp Characterizations Of The Infusion Balloon Surfacementioning
confidence: 43%
“…This result is in agreement with the literature as PAT significantly decreases the SM a-actin expression. 21,22 Also, in this study, no significant difference in the SM a-actin expression was observed between the cells treated with Cremophor-PAT and nab-PAT.…”
Section: Sem and Osp Characterizations Of The Infusion Balloon Surfacementioning
confidence: 43%
“…Exposure to local cerebral ischemia induces protein expression of ICAM-1 and GFAP. 37,51 Our data reveal that the expression levels of ICAM-1 and GFAP after I/R-induced cerebral injury were remarkably increased, while they were depressed after pretreatment with TNF-α or TNF-α/PEGb-(PELG-g-PLL). TNF-α or TNF-α/PEG-b-(PELG-g-PLL) pretreatment had a neuroprotective effect against BI/RI, and this effect was related to the inhibition of oxidative stress, inflammation, and apoptosis via reduction in both the expression of ICAM-1, GFAP, and caspase-3 and the levels of IL-6, IL-8, NO, and MDA, as well as increases in SOD activity and the levels of IL-4 and IL-10.…”
mentioning
confidence: 74%
“…It has been indicated that fluorofenidone protects against renal fibrosis by inhibiting STAT3 tyrosine phosphorylation [12]. And Zhang et al[8] found that Paclitaxel attenuates renal interstitial fibroblast activation and interstitial fibrosis by inhibiting STAT3 signaling. In our study, when treated with PAE, both in vivo and in vitro, the JAK2 and STAT3 tyrosine phosphorylation was inhibited and after that the process of renal fibrosis has been delayed.…”
Section: Discussionmentioning
confidence: 99%
“…And it has been reported to mediate various cellular functions, including gene activation, cell differentiation, cell survival, and proliferation [7]. STAT3 is an important member of the STAT family and mediates cell survival and proliferation [8]. Increasing evidence has suggested that the STAT3 pathway is highly related to renal fibrosis.…”
Section: Introductionmentioning
confidence: 99%